Hybird Autokey Cipher Algorithm Implementation Reverse Key and Standard Data Encryption for App-Based Text Messages - Lazuardi, Risandio Ilham; Anwar, Nuril (Universitas Ahmad Dahlan, 2023)
The development of the internet facilitates public communication in sharing information. Along with the advancement of technology in the communication segment, there were various threats to it. Many applications had sophisticated security systems, but the actions in exploiting these security systems were also increasingly diverse. This study implemented a combination of classic and modern algorithms, namely autokey cipher reverse key and DES to protect data from these crimes. This research develops encryption and decryption applications using the agile method, the technique used because of the time spent on the built progress of applications with a cycle for the development process. With this cycle utilized, the method was suitable for developing applications in the short term and revising or improving applications in each cycle. The research resulted in security applications having the function of helping people secure data so that they could prevent and complicate digital criminal acts.